Promosi Kesehatan Upaya Pencegahan COVID 19 Bekerja Sama Dengan Relawan Mahasiswa dan Desa Dilem - Yahmi Ira Setyaningrum; Alifia Candra Puriastuti (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2021)
The COVID 19 was spread in the word, also in Indonesian. The spread so fast became pandemic. STIKes WCH contribute to handle the pandemic disaster by promote and preventive action to minimized illness in Dilem village. The objective of the community service is minimized infect virus by health promote. Method education health with coordinated between LPPM STIKes WCH, voluntary COVID, head village Dilem. The activity was database people transmission from out city, disinfection spay, health promote to prevent COVID 19 by 3M activity. 3 M are using mask, wash hand, keep social distance. The result show community cooperative in this activity. The spray disinfection activity was doing without any problem. Health promote was increase knowledge community and active participate to provide facility to prevent contagious disease. The conclusion from the community service activity to decrease spreads infection by persuade people. The hope from next activity health promote add topic about nutrition to increase immune.